Antibacterial Effect of Plant Resin Collected from Tetrigona apicalis (Smith, 1857) in Thung Salaeng Luang National Park, Phitsanulok - KRAIKONGJIT, Sathirapong; JONGJITVIMOL, Touchkanin; MIANJINDA, Naklao; SIRITHEP, Nutta; KAEWBOR, Thodsaporn; JUMROON, Noppadon; JONGJITWIMOL, Jirapas (Walailak Journal of Science and Technology (WJST), 2017)
Tetrigona apicalis (Smith, 1857) is a common species of stingless bee found in lower northern Thailand. In previous studies, the propolis of stingless bees has been shown to have antibacterial properties, due to its chemically contained phenolic contents. The major component of propolis is resin. The purpose of this study, therefore, was to evaluate the antibacterial activities of crude resin extracts by disk diffusion and broth microdilution methods. We also determined the total phenolic contents using the Folin-Ciocalteau method and, to detect individual polyphenolic contents, we used the high performance liquid chromatographic method. Two samples of resin were collected from Thung Salaeng Luang National Park, Phitsanulok. The first sample was from fresh plants, which stingless bees used for nest construction. The second sample was taken from entrances of the bee’s nest. All samples were macerated in 30 % ethanol and incubated at room temperature for 14 days. The supernatants were filtered and ethanol residues then removed as ethanolic resin extracts (eREs). The antibacterial activity of the extracted resins against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853 was examined. The disks containing 9 and 14 mg of eREs produced obvious inhibition zones against S. aureus, but did not show zones against E. coli and P. aeruginosa. The minimum inhibitory concentrations (MICs) of the eREs against the bacterial strains tested were variously between 6 and 48 mg/ml, whereas the minimum bactericidal concentrations (MBCs) were from 12 to 48 mg/ml. The amount of the total phenolic compounds in the eREs from the fresh resin was 9,908 mg of pyrogallol equivalent (PGE) per kg of eREs, and from the nest entrances, 14,740 mg per kg. We also found that hydroquinin had the highest concentration in both extracts. In conclusion, the crude resin extracts demonstrated antibacterial properties against the S. aureus, E. coli, and P. aeruginosa strains tested. They also contained phenolic compounds which were active antibacterial agents. We have identified new and novel knowledge which can be used as preliminary data, leading to further, more detailed, investigation of the mechanistic action of the resin against bacterial cells.